Analisis Pengaruh Mineral terhadap Nilai Kuat Tekan Batuan - Noviandra Eko Putra; Shalaho Dina Devy; Agus Winarno (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
To determine the mineral content and composition of a rock, a petrographic test is carried out using a thin section method. Petrographic test is known as an efficient test of time and energy with accurate results in obtaining the composition and mineral content of rocks. The Point Load test is an index test that has been widely used to predict the UCS value of a rock indirectly in the field. This is due to the simple test procedure, easy sample preparation and can be done in the field, so that the strength of the rock can be quickly known in the field before testing in the laboratory.